Comparison of short- with long-term regeneration results after digital nerve reconstruction with muscle-in-vein conduits - Jennifer Lynn Schiefer; Lukas Schulz; Rebekka Rath; Stéphane Stahl; Hans-Eberhard Schaller; Theodora Manoli (Neural Regeneration Research, 2015)
Muscle-in-vein conduits are used alternatively to nerve grafts for bridging nerve defects. The purpose of this study was to examine short- and long-term regeneration results after digital nerve reconstruction with muscle-in-vein conduits. Static and moving two-point discriminations and Semmes-Weinstein Monofilaments were used to evaluate sensory recovery 6-12 months and 14-35 months after repair of digital nerves with muscle-in-vein in 7 cases. Both follow-ups were performed after clinical signs of progressing regeneration disappeared. In 4 of 7 cases, a further recovery of both two-point discriminations and in another case of only the static two-point discrimination of 1-3 mm could be found between the short-term and long-term follow-up examination. Moreover, a late recovery of both two-point discriminations was demonstrated in another case. Four of 7 cases showed a sensory improvement by one Semmes-Weinstein Monofilaments. This pilot study suggests that sensory recovery still takes place even when clinical signs of progressing regeneration disappear.